2018
DOI: 10.3892/ol.2018.8109
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑216b reduces growth, migration and invasion of pancreatic ductal adenocarcinoma cells by directly targeting ρ‑associated coiled‑coil containing protein kinase 1

Abstract: Abstract. Developments in cancer therapy have greatly improved the survival time for patients with pancreatic ductal adenocarcinoma (PDAC); however, the prognosis of patients with PDAC remains poor. Understanding the expression patterns and functions of microRNAs may provide strategies for the diagnosis and treatment of patients with PDAC. The present study aimed to explore the expression and functions of microRNA-216b (miR-216b) in PDAC. The expression of miR-216b in PDAC tissues and cell lines was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Accumulating evidence reveals that miRNA dysfunction influences the metastasis, chemo-radioresistance and overall survival time of patients with cancer, including patients with PDAC (7)(8)(9)(10). Previous reports have revealed miRNA involvement in PDAC progression, including roles of miR-216b (11), miR-10a-5p (10), miR-374b-5p (12), miR-1271 (13), miR-7-5p (14), miR-4295 (15) and miR-185 (16). However, the molecular mechanisms underlying the involvement of miRNAs in PDAC progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence reveals that miRNA dysfunction influences the metastasis, chemo-radioresistance and overall survival time of patients with cancer, including patients with PDAC (7)(8)(9)(10). Previous reports have revealed miRNA involvement in PDAC progression, including roles of miR-216b (11), miR-10a-5p (10), miR-374b-5p (12), miR-1271 (13), miR-7-5p (14), miR-4295 (15) and miR-185 (16). However, the molecular mechanisms underlying the involvement of miRNAs in PDAC progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-155-5p promotes autophagy in cervical cancer cells by targeting PDK1 and further inhibits the tumor progression in cervical cancers. Further, miRNA-216b increases growth, migration, and invasion, and serves as a tumor suppressor in pancreatic ductal adenocarcinoma (10). In addition, miRNA-1269 promotes cell survival and accelerates the proliferative ability of lung cancer cells by inhibiting its target gene TP53 (11).…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with these data, Liu et al [33] have recently reported that the level of miR-216b in PDAC cells (Panc-1, BxPC3 and SW 1990) is 3-to 4-fold lower than in non-cancer cells. The targets of miR-216b in PDAC cells include TPT1, a gene encoding for the translationally-controlled tumor protein [34], and ROCK1, the ρ-associated coiled-coil containing protein kinase 1 [33]. In addition, miR-216b targets the KRAS oncogene in nasopharyngeal tumor cells [35].…”
Section: Resultsmentioning
confidence: 56%